KAJIAN EKONOMI POLITIK BANTUAN MODAL MASYARAKAT MISKIN STUDI KASUS KEBIJAKAN BANTUAN DANA PELAKU USAHA MIKRO (UKM) DI KABUPATEN BANTUL - Riawanti, Wahyu (Optimum: Jurnal Ekonomi dan Pembangunan, 2014)
Small and Medium Enterprises (SME) is the main sector to prevent developing countries from collapse during the economy crises. Meanwhile in Indonesia, not many policies in SME seem to stand in the right place in helping the SME actors especially the mikro business people. This research aimed to study about the implementation of government aid program in two sub-district in Bantul and how the micro business people perspective about those program. Using triangulation of qualitative and quantitative methods, this research tried to combine those insight and fi ndings from the two different data sources. Result in early qualitative research of study has shown two main reasons of government aid program implementation characters: (a) inefective program caused by beureucrate and (b) distrust of community. The following quantitative research was organised to confi rm and emphasize the indicators. Data of questionnaire confi rmed that distrust of people came from the ineffi cient beaurocrate. It also emerged the fact about complexity of program came from the jealousy between benefi ciaries has made the programs less efective.